Upaya Perlindungan Lingkungan Hidup Melalui Pembangunan Ruang Terbuka Hijau Oleh Pemerintah Daerah - Paskalis Hananta Wihardjo (Comprehensive Law Journal, 2024)
The Local Government of Malang City has made efforts to provide and increase green open space in Malang City such as revitalizing green open space, procuring new land for green open space and requiring developers to submit their green open space land to the Government. Efforts made by the Malang City government resulted in a green open space area of 19.4%, 9.4% public green open space and 10% private. The green open space of an urban area should have 30% of the area of an urban area. Based on the results of research and interviews, the author observes that the amount of green open space in Malang City has not met the predetermined amount of 30% of the area of Malang City. The government has tried to organize adequate green open space, but there are still obstacles found such as the decreasing land in urban areas, the budget for green open space related agencies that are not sufficient to buy land that will be used as green open space. The government needs to conduct socialization and movements to make people aware of the importance of the environment, especially green open spaces.